The political philosophy of Jean-Jacques Rousseau : the impossibility of reason - Qvortrup, Matt (Manchester University Press ; Distributed exclusively in the USA by Palgrave, 2003)
The first comprehensive analysis of Rousseau's political philosophy for a generation, this timely book rejects the authoritarian reading of Rousseau and establishes him as an anti-revolutionary closer to Burke than to Robespierre.